The Tick Protein Sialostatin L2 Binds to Annexin A2 and Inhibits NLRC4-Mediated Inflammasome Activation - Wang, Xiaowei; Shaw, Dana K; Sakhon, Olivia S; Snyder, Greg A; Sundberg, Eric J; Santambrogio, Laura; Sutterwala, Fayyaz S; Dumler, J Stephen; Shirey, Kari Ann; Perkins, Darren J; Richard, Katharina; Chagas, Andrezza C; et al. (Infection and immunity, 2016)
Tick saliva contains a number of effector molecules that inhibit host immunity and facilitate pathogen transmission. How tick proteins regulate immune signaling, however, is incompletely understood. Here, we describe that loop 2 of sialostatin L2, an anti-inflammatory tick protein, binds to annexin A2 and impairs the formation of the NLRC4 inflammasome during infection with the rickettsial agent Anaplasma phagocytophilum Macrophages deficient in annexin A2 secreted significantly smaller amounts of interleukin-1β (IL-1β) and IL-18 and had a defect in NLRC4 inflammasome oligomerization and caspase-1 activation. Accordingly, Annexin a2-deficient mice were more susceptible to A. phagocytophilum infection and showed splenomegaly, thrombocytopenia, and monocytopenia. Providing translational support to our findings, better binding of annexin A2 to sialostatin L2 in sera from 21 out of 23 infected patients than in sera from control individuals was also demonstrated. Overall, we establish a unique mode of inflammasome evasion by a pathogen, centered on a blood-feeding arthropod.
Keywords: Cystatins; Gene Expression Regulation; Protein Binding; Protein Isoforms; Annexin A2; Recombinant Proteins; proteiny regulující apoptózu; klíště; iniciační kaspasy; signální transdukce; Amino Acid Sequence; Apoptosis Regulatory Proteins; interleukin-1beta; Arachnid Vectors; kaspasa 1; Escherichia coli; Anaplasma phagocytophilum; protein - isoformy; Immune Evasion; imunitní únik; Signal Transduction; Inflammasomes; molekulární modely; Interleukin-18; annexin A2; Caspases; Caspase 1; rekombinantní proteiny; Models, Molecular; kaspasy; arachnida jako vektory; vazba proteinů; interleukin-18; Animals; lidé; Humans; zvířata; regulace genové exprese; Calcium-Binding Proteins; makrofágy; cystatiny; sekvence aminokyselin; inflamasomy; proteiny vázající vápník; myši; Interleukin-1beta; Ixodes; ehrlichióza; Caspases, Initiator; Mice; Macrophages; Ehrlichiosis